Great Zimbabwe's water - Pikirayi, I.; Sulas, F.; Musindo, T.T.; Chimwanda, A.; Chikumbirike, J.; Mtetwa, E.; Nxumalo, B.; Sagiya, M.E. (Wiley, 2021)
Once a thriving center with commercial links to the Indian Ocean, what remains of Great Zimbabwe is its monumental architecture. Its rise and decline have long been linked to environmental changes in southern Zimbabwe, beginning in the second half of the 13th century with agropastoralists thriving in the region's well-watered granite hills and valleys, and culminating in a vast urban and trading society. Later, c.1550 AD, it is argued, drying climate, land overexploitation, and changing regional trading patterns would lead to the decline of Great Zimbabwe. A review of this model is necessary since Great Zimbabwe and communities living around it survive in a region constantly threatened by water crises. However, we still know very little on the forms and uses of water and how these have influenced its development and demise. This article offers a multilayered review of available information on water, including new records on environmental sequences, modern water sources, and provisioning models from in and around Great Zimbabwe. The integration of both old and new datasets allows us to follow the history of people-water interaction from early times to the present. We argue that understanding of the local environment was vital in managing both water excesses and shortages in the past, and show that some of this knowledge survives among indigenous communities linked to the site and living in the surrounding landscape. While nearby Masvingo town has persistently lived under water-emergency conditions, farmers around Great Zimbabwe mitigate shortfalls of modern water provision through a balanced and mutually vital interaction with natural water resources such as springs and soil moisture.